Patient Experience in The Healing Process of Tuberculosis: A Phenomenology Study - Resti Yulianti Sutrisno; Dewi Rossytalia Widiyastuti; Arif Wahyu Setyo Budi; Bertha Tesma Wulandari; Kellyana Irawati; Passakorn Suanrueang (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Indonesia has the third rank of the highest tuberculosis (TB) incidents globally. The complete treatment of the disease becomes the essential thing to be conducted. The duration of TB treatment for at least six months and various factors can affect mental health to the occurrence of depression. The presence of depression in TB patients was significantly associated with poor adherence to TB treatment, as well as higher rates of treatment failure and higher mortality rates. Objective: Exploring the experience of tuberculosis patients during the healing process related to the risk factors that cause depression in patients.Method: A qualitative study with a phenomenological approach. The purposive sampling technique collected nine participants from five public health centers in The District of Sleman. They were patients with pulmonary tuberculosis who underwent treatment in the intensive or the continuous phase, presence of depression based on screening with the Beck Depression Inventory-II Questionnaire. Data were collected by conducting in-depth interviews and were analyzed using inductive content analysis. Result: There are five themes as the factors that cause depression in patients with pulmonary tuberculosis which are a) denial of destiny, b) stigma about tuberculosis, c) presence of comorbidities, d) no family support, and e) losing a job.Conclusion: Factors causing depression in TB patients are denial of destiny, stigma about tuberculosis, comorbidities, no family support, and losing a job. It is crucial for health workers to provide health education, counseling, and psychotherapy community-based intervention related to disease, stigma prevention, and family support to reduce the incidence of depression so that they can help complete treatment.